2017
DOI: 10.1007/s10919-017-0261-4
|View full text |Cite
|
Sign up to set email alerts
|

How What We See and What We Know Influence Iconic Gesture Production

Abstract: In face-to-face communication, speakers typically integrate information acquired through different sources, including what they see and what they know, into their communicative messages. In this study, we asked how these different input sources influence the frequency and type of iconic gestures produced by speakers during a communication task, under two degrees of task complexity. Specifically, we investigated whether speakers gestured differently when they had to describe an object presented to them as an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…It seems likely the spatial characteristics of the objects were particularly salient after seeing the objects depicted. In contrast, Masson-Carro et al (2017) found that participants were more likely to produce gestures that mimicked holding or interacting with objects when they described objects that are readily manipulable (e.g., a tennis racket), and they produced such gestures most often when they had read the name of the object rather than seen it depicted. It seems likely that manipulable objects activate motor imagery more strongly than spatial imagery, particularly when the objects' spatial characteristics have not just been viewed.…”
Section: Review Of Evidencementioning
confidence: 81%
See 3 more Smart Citations
“…It seems likely the spatial characteristics of the objects were particularly salient after seeing the objects depicted. In contrast, Masson-Carro et al (2017) found that participants were more likely to produce gestures that mimicked holding or interacting with objects when they described objects that are readily manipulable (e.g., a tennis racket), and they produced such gestures most often when they had read the name of the object rather than seen it depicted. It seems likely that manipulable objects activate motor imagery more strongly than spatial imagery, particularly when the objects' spatial characteristics have not just been viewed.…”
Section: Review Of Evidencementioning
confidence: 81%
“…Although speculative, there is some empirical support for this explanation that the effect of stimulus presentation modality can depend on aspects of the communicative situation. Masson-Carro, Goudbeek, and Krahmer (2017) found that participants gestured more when describing an object to someone else when the object was indicated with a picture than when it was indicated with a verbal label. The effect disappeared, however, when the task was made more difficult by preventing participants from naming the object, perhaps because participants adopted a very different strategy when not allowed to use the name.…”
Section: Review Of Evidencementioning
confidence: 92%
See 2 more Smart Citations
“…Additionally, when reading a word or seeing an image of an object, the different types of information inform different forms of gestural expression. Researchers have demonstrated that seeing an image of an object leads to more gesture specifically depicting the physical characteristics of the object, whereas reading the name of an object is correlated with relatively less gesture production but the produced gestures are focused on the utility of the object (Masson-Carro et al 2017). Furthermore, objects with high affordances are associated with more representational gestures and with gestures based on how the object is manipulated in the real world (Masson-Carro et al 2016).…”
Section: Introductionmentioning
confidence: 99%